2016
DOI: 10.1109/access.2016.2633378
|View full text |Cite
|
Sign up to set email alerts
|

Pose Determination of a Robot Manipulator Based on Monocular Vision

Abstract: This paper presents an approach to determine the pose of a robot manipulator by using a single fixed camera. Conventionally, the pose determination is usually achieved by using the encoders to sense the joint angles, and then the pose of the end effector is obtained by using the direct kinematics of the manipulator. However, when the encoders or the manipulators are malfunctioning, the pose may not be accurately determined. This paper presents an approach based on machine vision, where a single camera is fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…First, N object points (vertices) which are randomly distributed in the range of [−2, 2] × [−2, 2] × [4,8] are generated. Next, the object is rotated to an arbitrary orientation and translated to arbitrary point according to a generated pose which can be denoted by R true and T true .…”
Section: Simulations and Experiments Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, N object points (vertices) which are randomly distributed in the range of [−2, 2] × [−2, 2] × [4,8] are generated. Next, the object is rotated to an arbitrary orientation and translated to arbitrary point according to a generated pose which can be denoted by R true and T true .…”
Section: Simulations and Experiments Resultsmentioning
confidence: 99%
“…Pose estimation is widely used in virtual reality [1], unmanned air vehicle navigation [2], aircrafts docking [3] and robot control [4]. In industrial measurement, point-based pose estimation is computing the pose of an object through 3D known geometry and the corresponding 2D image, which is also known as the PnP (perspective-n-point) problem [5].…”
Section: Introductionmentioning
confidence: 99%
“…R OBOTIC manipulators usually rely on data obtained from rotary encoders to determine their joint angles and to relay it to a closed-loop control system. However, rotary encoders have flaws [1], [2], due to effects of elastic joints, joint frictions, flexible links, gearbox backlashes, etc [1]. Furthermore, using an incremental rotary encoder requires an absolute position sensor, such as a hall sensor, to obtain a reference point, and requires the current position saved in memory before shutting down the system.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that their system is reliable in real-world applications with millimetric and near 0°errors. Kuo et al [1] proposed a single cam-era vision-based system for estimating a manipulator joint angles. The authors used visual markers and pointed at the manipulator with a fixed camera.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation